Is corporate R&D investment in high-tech sectors more effective? Some guidelines for European Research Policy - Raquel Ortega-Argilés; Mariacristina Piva; Lesley Potters; Marco Vivarelli (Institute for the Study of Labor (IZA), 2009)
This paper discusses the link between R&D and productivity across the European industrial and service sectors. The empirical analysis is based on both the European sectoral OECD data and on a unique micro longitudinal database consisting of 532 top European R&D investors. The main conclusions are as follows. First, the R&D stock has a significant positive impact on labour productivity; this general result is largely consistent with previous literature in terms of the sign, the significance and the magnitude of the estimated coefficients. More interestingly, both at sectoral and firm levels the R&D coefficient increases monotonically (both in significance and magnitude) when we move from the low-tech to the medium and high-tech sectors. This outcome means that corporate R&D investment is more effective in the high-tech sectors and this may need to be taken into account when designing policy instruments (subsidies, fiscal incentives, etc.) in support of private R&D. However, R&D investment is not the sole source of productivity gains; technological change embodied in gross investment is of comparable importance on aggregate and is the main determinant of productivity increase in the low-tech sectors. Hence, an economic policy aiming to increase productivity in the low-tech sectors should support overall capital formation.
urn:nbn:de:101:1-20090209152
Keywords: O33; 330; R&D; productivity; high-tech sectors; innovation; industrial policy; Industrielle Forschung; Arbeitsproduktivität; Low-Tech; Hochtechnologiesektor; Forschungs- und Technologiepolitik; OECD-Staaten; EU-Staaten